2004
DOI: 10.1038/sj.onc.1207766
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine phosphatase PTPRJ/DEP-1 genotype affects thyroid carcinogenesis

Abstract: We recently isolated the r-PTPeta gene, which encodes a receptor-type tyrosine phosphatase protein that suppresses the neoplastic phenotype of retrovirally transformed rat thyroid cells. The human homologue gene PTPRJ/DEP-1 is deleted in various tumors. Moreover, the Gln276Pro polymorphism, located in the extracellular region of the gene, seems to play a critical role in susceptibility to some human neoplasias. Here we report the loss of heterozygosity (LOH) of PTPRJ in 11/76 (14.5%) informative thyroid tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 29 publications
2
69
0
2
Order By: Relevance
“…There- Western blot analysis showed that dephosphorylation of c-Src tyrosine 529, and FAK and paxillin tyrosine phosphorylation in PC MPSV cells are proportional to the levels of r-PTPZ expression. These results have important implications for tumor biology because of the loss of heterozygosity of PTPRJ, the human homolog of r-PTPZ, found in several colon, lung, breast and thyroid cancers (Ruivenkamp et al, 2002;Iuliano et al 2004). Finally, very recently, DEP1/PTPRJ expression levels were found to be drastically reduced or absent also in human pancreatic cancer cells .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…There- Western blot analysis showed that dephosphorylation of c-Src tyrosine 529, and FAK and paxillin tyrosine phosphorylation in PC MPSV cells are proportional to the levels of r-PTPZ expression. These results have important implications for tumor biology because of the loss of heterozygosity of PTPRJ, the human homolog of r-PTPZ, found in several colon, lung, breast and thyroid cancers (Ruivenkamp et al, 2002;Iuliano et al 2004). Finally, very recently, DEP1/PTPRJ expression levels were found to be drastically reduced or absent also in human pancreatic cancer cells .…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, in a recent paper (Massa et al, 2004), the correlation between the expression of r-PTPZ and the responsivity to the antiproliferative effects of the somatostatin has been demonstrated in glioma cells, indicating that the expression levels of r-PTPZ are also critical in other r-PTPZ-dependent pathways. In addition, it has been suggested that PTPRJ polymorphisms differ in their tumor suppressor activity (Ruivenkamp et al, 2002;Iuliano et al 2004), and it would be intriguing to find whether distinct PTPRJ forms exert different effects on the pathway described herein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable Ptprj loss of heterozygosity has been identified in human colon, mammary, lung, and thyroid carcinomas (13,14). Moreover, the Gln 276 Pro Ptprj polymorphism is implicated in susceptibility to various human cancers (11), whereas the Gln 276 Pro, Arg 326 Gln, and Asp 872 Glu polymorphisms have been associated with thyroid carcinoma (15). Ptprj expression was found to be reduced in in vitro-transformed thyroid follicular cells (2) and in primary specimens of human papillary thyroid carcinomas (PTC; ref.…”
Section: )]mentioning
confidence: 99%
“…In accordance with previous studies, we found a strong linkage disequilibrium between both CD148 Q276P and R326Q polymorphisms. 26 Importantly, our results suggested that CD148 Q276P and R326Q polymorphisms influence the pathogenicity of PF4/H antibodies but not the immune response to heparin because the minor allele frequency was different between HIT and Ab pos patients, but not between Ab neg and Ab pos controls.…”
Section: Discussionmentioning
confidence: 81%